Effect of Scapular Retraction on Lower Trapezius, Infraspinatus, and Deltoid Muscle Electromyographic Activity During the Side-Lying Abduction Exercise - Masaaki Tsuruike; Todd S. Ellenbecker (North American Sports Medicine Institute, 2023)
# Background The lower trapezius (LT) muscle, which stabilizes the scapula posteriorly during arm elevation, has been interesting to both clinicians and researchers for its importance in throwing-related shoulder rehabilitation and injury prevention. # Purpose The purpose of this study was to investigate the electromyographic activity of the LT and other relevant muscles during scapular and shoulder activities in the side-lying position. # Methods Twenty collegiate baseball players volunteered to participate in this study. Electromyographic (EMG) output of the lower trapezius, infraspinatus, posterior deltoid, middle deltoid, serratus anterior, and upper trapezius muscles were collected. All the subjects performed isometric resistance exercises in four arm positions: 0° horizontal abduction from the coronal plane (NEUT) with protraction (NEUT-PRO), 15° horizontal adduction from the coronal plane (HADD) with protraction (HADD-PRO), and NEUT with retraction (NEUT-RET), and HADD-RET in a side-lying isometric abduction exercise with two external loads: a 9.1 kg dumbbell and 40% of the manual muscle test (MMT). The subjects also performed two more isometric resistance exercises: supine protraction and side-lying external rotation (ER) of the glenohumeral (GH) joint in GH adduction at 90° of GH ER or with as much ER as possible. All raw EMG data were normalized to maximal voluntary isometric contraction (% MVIC) of the corresponding muscle. # Results LT activity was significantly greater in HADD-RET with 9.1 kg than that of HADD-PRO (p \< 0.001) (55 vs 21% MVIC) while middle deltoid muscle activity was significantly decreased in both NEUT and HADD-RET compared to that of NEUT and HADD-PRO (p \< 0.001). In contrast, IS muscle activity was significantly increased in HADD-RET with 9.1 kg compared with that 40% MMT (p \< 0.001) (41 vs 22% MVIC). # Conclusion LT activity was modulated by changes in scapulothoracic and glenohumeral joint positioning during a side-lying isometric abduction exercise. These findings may help clinicians to select exercises to improve scapular muscle balance ratios during rehabilitation of the shoulder complex. # Level of Evidence Level 3b, Controlled laboratory study